Budaya Politik Pemuda Batak Di Gereja HKBP Simpang Marindal : (Studi Terhadap Partisipasi Politik Pilpres 2024) - Adelina Sitanggang; Bertania Permata Sari; Dyna M.T Pasaribu; Fahrysyah Aulya; Mhd. Iraqi Fauzi; Mira Cahya; Nur Hidayah Hasibuan; Prayetno Prayetno (Pusat Riset dan Inovasi Nasional, 2024)
This research aims to understand the political culture of Batak youth at the HKBPSimpang Marindal Church and how this political culture influences youth political participation in the 2024 presidential election. This research was conducted by analyzing the values, beliefs, norms and political practices of the younger generation in Batak society . The research method used is a descriptive method with data collection through questionnaires and documentation, as well as qualitative data analysis. The results of the research show that the political culture of Batak youth at the HKBPSimpang Marindal Church has a significant influence on youth political participation in the 2024 presidential election. The values ​​and norms adhered to by Batak youth in the context of the church influence their attitudes towards politics, trust in political institutions, preferences for candidates or political parties, as well as their involvement in political activities such as campaigns and voting. This research provides in-depth insight into how the young Batak generation is involved in the political process and how their political cultural factors influence political participation in the 2024 presidential election. The results of this research can be an important basis in understanding the role of youth in developing democracy in Indonesia.